Left Ventricular End-Diastolic Pressure and B-Type Natriuretic Peptide Levels Guidance of Low-Dose Furosemide Treatment to Prevent Contrast-Induced Nephropathy in Patients with Percutaneous Coronary Intervention: A Randomized Controlled Trial - Guoqiang Gu (Hindawi-Wiley, 2021)
Objective. We aimed to explore the preventive effect of low-dose furosemide administration guided by left ventricular end-diastolic pressure (LVEDP) and B-type natriuretic peptide (BNP) based on adequate hydration on contrast-induced nephropathy (CIN) in patients with percutaneous coronary intervention (PCI). Methods. This parallel randomized clinical trial was conducted at a tertiary hospital in China. A total of 1053 consecutive patients (71.98% men) who underwent PCI at our hospital were enrolled. Pre-PCI plasma BNP levels were recorded. Patients enrolled received a continuous intravenous infusion of normal saline starting 4 h before PCI until 24 h after surgery. LVEDP was measured immediately after surgery. Patients in the control group received intravenous furosemide injection (20 mg). Patients in the experimental group received furosemide if they showed LVEDP ≥15 mmHg, a post-PCI BNP level ≥100 pg/mL, and/or a post-PCI BNP value > 150% of the pre-PCI value. The primary and secondary outcome measures were serum creatinine levels, glomerular filtration rate, and creatinine clearance rate measured before and after PCI. CIN incidence was compared between the two groups. Logistic regression analysis was used to study the risk factors for CIN. Results. CIN incidence was significantly higher in the control group than in the experimental group (P<0.05). Logistic regression analysis showed that elevated LVEDP and BNP levels were risk factors. As LVEDP increased, the CIN incidence also increased (odds ratio (OR) 1.038, 95% confidence interval (CI) 1.006–1.070). The OR of BNP was 1.001 (95% CI 1.000–1.002). Conclusions. Low-dose furosemide administration guided by LVEDP or BNP is superior to direct low-dose administration on the basis of adequate hydration during PCI. This trial is registered with ChiCTR-IOR-14005250